The Economic Partnership Between the Netherlands and Usa - Razvan Hagima (CES Working Papers, 2014)
The economic relations between The Netherlands and USA represent an important pylon for the economic environment from both countries. USA is the main investor in the Netherlands because of it' fiscal policies but the European country, despite of its small area, it is ranked in top 5 investors in US. Only in Texas about 70000 jobs were created by the Dutch investors so it's clear to see that this partnership brings mutual benefits for both countries.
Keywords: G01; E00; 330; foreign direct investment; trade; job Romania